Marcas narrativas da cultura do estupro no ciberespaço - análise da misoginia contra Dilma Rousseff - Vieira, Pâmela Rocha (2018)
This dissertation investigates the narrative marks of the rape culture against the first woman to occupy the position of the presidency of Brazil, Dilma Rousseff. The cyberterritory space, with an emphasis on Social Networking on the Internet, is ou focus in the search for understanding symbolic manifestations of violence against women, especially when these women occupy spaces of power and challenge the gender stereotype, suffering retaliation related to the concept of rape culture.